A new short and simple health-related quality of life measurement for paediatric rheumatic diseases: initial validation in juvenile idiopathic arthritis - Filocamo, Giovanni; Schiappapietra, Benedetta; Bertamino, Marta; Pistorio, Angela; Ruperto, Nicolino; Magni-Manzoni, Silvia; Lanni, Stefano; Saad-Magalhaes, Claudia [UNESP]; Galasso, Roberta; Lattanzi, Bianca; Muratore, Valentina; Tani, Daniela; et al. (Oxford University Press, 2010)
Objective. To develop and validate a new short and simple measure of health-related quality of life (HRQL) in children with juvenile idiopathic arthritis (JIA).Methods. The Paediatric Rheumatology Quality of Life Scale (PRQL) is a 10-item questionnaire that explores HRQL in two domains: physical health (PhH) and psychosocial health (PsH). Validation of the parent proxy report and child self-report versions of the instrument was accomplished by evaluating 472 JIA patients and similar to 800 healthy children. Validation analyses included assessment of feasibility, face and content validity; construct and discriminative ability; internal structure and consistency; test-retest reliability; responsiveness to clinical change; and minimal clinically important difference.Results. The PRQL was found to be feasible and to possess both face and content validity. The PRQL score correlated in the predicted range with most of the other JIA outcome measures, thereby demonstrating good construct validity, and discriminated well between different levels of disease severity. Assessment of internal structure (factor analysis) revealed that the PhH and PsH subscales identify two unambiguously separated domains. The internal consistency (Cronbach's alpha) was 0.86. The intraclass correlation coefficient for test-retest reliability was 0.91. The PRQL revealed fair responsiveness, with a standardized response mean of 0.67 in improved patients. Overall, the PRQL appeared to be more able to capture physical HRQL than psychosocial HRQL.Conclusion. The PRQL was found to possess good measurement properties and is, therefore, a valid instrument for the assessment of HRQL in children with JIA. This tool is primarily proposed for use in standard clinical care.
Keywords: Rheumatic diseases; Health-related quality of life; Paediatrics; Children; Adolescents